First record of Melanaphis sorghi (Theobald, 1904) (Hemiptera aphididae) in Italy and Spain - Casiraghi, Alice; Addelfio, Nicola; Ardenghi, Nicola M. G.; Pérez-Hidalgo, Nicolás (Council for Agricultural Research and Economics (CREA), 2024)
The sorghum aphid Melanaphis sorghi (Theobald) is recorded for the first time in mainland Italy (Florence, Tuscany region, Italy) and Spain (Vinalesa, Valencia Region, Spain) on Sorghum halepense (L.) Pers. Data on its biology, worldwide distribution and notes on its pest behaviour are given. Melanaphis sorghi had previously been recorded from Greece (in 2008), Cyprus and Israel. The records of this species in Iran and Turkey need confirmation.